Representasi Perempuan Muslim dalam Dakwah Digital: Analisis Wacana Sara Mills pada Sepuluh Postingan Instagram @muslimahdaily - Muhammad Hubal Khoir, Emil (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
This study examines the representation of Muslim women in digital da'wah content on Instagram through Sara Mills’ discourse analysis. Instagram, as a visual-based platform, has become an important medium in shaping gender narratives, especially in contemporary Islamic discourse. The account @muslimahdaily was selected because it consistently produces content related to women’s piety, mental well-being, religious ethics, and modern Muslim identity. Ten posts were analyzed to reveal how subject–object relations and reader positioning construct meaning about Muslim women. The findings show that the account frames women as moral and religious subjects who are expected to embody patience, emotional discipline, and adherence to Islamic ethics. At the same time, women are positioned as vulnerable individuals who require guidance and protection, especially in navigating social pressures, digital phenomena, and religious obligations. The discourse also integrates Islamic values with modern lifestyle aesthetics, creating a hybrid identity of the “modern yet devout Muslim woman.” This study concludes that digital da'wah on Instagram not only informs but also shapes gender ideology by forming a collective identity of “Sahabat Muslimah” (Muslimah Sisters) that follows specific moral expectations embedded in the content.